The river [large type] - Neale, Michael (Thorndike Press, 2012)
Gabriel is mysteriously drawn to a ribbon of frothy water carving its way through steep canyons high in the Colorado Rockies. From deep within, Gabriel's passion for the river is undeniable. The rushing waters beckon him to experience freedom, but something holds him back.